(x+y)*(x-y(*)x²+y²) please tell using identities step by step
Attachments:
![](https://hi-static.z-dn.net/files/dae/463ad9674f313eb89dda0f3f044b8f24.jpg)
Answers
Answered by
3
Identity used is,
![(a+b)(a-b) = a^{2}-b^{2} (a+b)(a-b) = a^{2}-b^{2}](https://tex.z-dn.net/?f=+%28a%2Bb%29%28a-b%29+%3D+a%5E%7B2%7D-b%5E%7B2%7D+)
![(x + y)( x - y)( {x}^{2} + {y}^{2} ) \\ = ( {x}^{2} - {y}^{2} )( {x}^{2} + {y}^{2} ) \\ = {x}^{4} - {y}^{4} (x + y)( x - y)( {x}^{2} + {y}^{2} ) \\ = ( {x}^{2} - {y}^{2} )( {x}^{2} + {y}^{2} ) \\ = {x}^{4} - {y}^{4}](https://tex.z-dn.net/?f=%28x+%2B+y%29%28+x+-+y%29%28+%7Bx%7D%5E%7B2%7D+%2B+%7By%7D%5E%7B2%7D+%29+%5C%5C+%3D+%28+%7Bx%7D%5E%7B2%7D+-+%7By%7D%5E%7B2%7D+%29%28+%7Bx%7D%5E%7B2%7D+%2B+%7By%7D%5E%7B2%7D+%29+%5C%5C+%3D+%7Bx%7D%5E%7B4%7D+-+%7By%7D%5E%7B4%7D+)
Hope it helps and mark as brainelist
Hope it helps and mark as brainelist
Answered by
4
here is ur answer mate
Attachments:
![](https://hi-static.z-dn.net/files/d25/05b20cc9e075d5f70d10705408a6a935.jpg)
Similar questions